2010
DOI: 10.1177/1475921710373296
|View full text |Cite
|
Sign up to set email alerts
|

Integrated seismic early warning and structural health monitoring of critical civil infrastructures in seismically prone areas

Abstract: A large part of Europe is exposed to medium/high seismic risk. Throughout the past decades serious structural damage and collapse have occurred in different countries. Examples of structures at risk are existing infrastructure and public buildings. Efficient seismic protection is especially required in these structures. In fact, an earthquake can lead to a high number of injury or death since these structures are often crowded. On the other hand, strategic structures have to be fully operational to manage the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 26 publications
0
37
0
2
Order By: Relevance
“…From the results of two case studies combining a realistic structural model and wireless simulations collected from real-world deployments, the authors concluded that both approaches improve structural control performance. Finally, Rainieri et al [2011] presented an overview on seismic early warning networks implemented worldwide, along with the development of integrated optimized structural health monitoring (SHM) technologies.…”
Section: Seismic Early Warning and Wireless Control Systemsmentioning
confidence: 99%
“…From the results of two case studies combining a realistic structural model and wireless simulations collected from real-world deployments, the authors concluded that both approaches improve structural control performance. Finally, Rainieri et al [2011] presented an overview on seismic early warning networks implemented worldwide, along with the development of integrated optimized structural health monitoring (SHM) technologies.…”
Section: Seismic Early Warning and Wireless Control Systemsmentioning
confidence: 99%
“…Wu et al (2010) present the monitoring of a historic tower in Trento, Italy, which provided valuable information about the structure and its behavior. Rainieri et al (2010) discuss integration of SHM systems with seismic early warning systems (SEWS). This concept is of special interest because the algorithm presented in this paper is potentially applicable to both types of monitoring, which would make the integration of those two systems much easier than with other algorithms.…”
Section: Applications Of Shmmentioning
confidence: 99%
“…This concept is of special interest because the algorithm presented in this paper is potentially applicable to both types of monitoring, which would make the integration of those two systems much easier than with other algorithms. Rainieri et al (2010) further discuss the possibility of using a city-wide system not only for monitoring and forewarning, but also for emergency management after a seismic event. Fabbrocino et al (2009) investigate SHM for retaining walls by means of instrumenting piles.…”
Section: Applications Of Shmmentioning
confidence: 99%
“…One of the most successful engineering applications of EEW is the Urgent Earthquake Detection and Alarm System (UrEDAS) of the Japan Railway Group [17] for the high-speed Shinkansen trains. Recently, the concept of integrating EEW with SHM in local damage detection [19] or global loss assessment [14] are mentioned by some research groups in Europe. In this paper, our aim is to development a complete synergistic framework between EEW and SHM to optimize the use of the information provided by both systems under a robust Bayesian probabilistic framework.…”
Section: Development Of Eew and Its Applicationsmentioning
confidence: 99%